2016
DOI: 10.3389/fnhum.2016.00468
|View full text |Cite
|
Sign up to set email alerts
|

Improving Production of Treated and Untreated Verbs in Aphasia: A Meta-Analysis

Abstract: Background: Demographic and clinical predictors of aphasia recovery have been identified in the literature. However, little attention has been devoted to identifying and distinguishing predictors of improvement for different outcomes, e.g., production of treated vs. untreated materials. These outcomes may rely on different mechanisms, and therefore be predicted by different variables. Furthermore, treatment features are not typically accounted for when studying predictors of aphasia recovery. This is partly du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 103 publications
1
8
0
Order By: Relevance
“…This result is generally in line with studies where verb naming has been targeted within a sentence context (Thompson et al 2013). It has been suggested that sentence level treatment may be more effective at encouraging generalization, because in addition to rebuilding specific knowledge of lexemes it trains the semantic and syntactic features associated with the verb (de Aguiar et al 2016). However, unlike other sentence level treatments (e.g., Thompson et al 2013), our therapy did not involve direct training of argument structure or morphology.…”
Section: Effects Of Treatment On Verb Namingsupporting
confidence: 85%
See 1 more Smart Citation
“…This result is generally in line with studies where verb naming has been targeted within a sentence context (Thompson et al 2013). It has been suggested that sentence level treatment may be more effective at encouraging generalization, because in addition to rebuilding specific knowledge of lexemes it trains the semantic and syntactic features associated with the verb (de Aguiar et al 2016). However, unlike other sentence level treatments (e.g., Thompson et al 2013), our therapy did not involve direct training of argument structure or morphology.…”
Section: Effects Of Treatment On Verb Namingsupporting
confidence: 85%
“…It has been suggested that sentence level treatment may be more effective at encouraging generalization, because in addition to rebuilding specific knowledge of lexemes it trains the semantic and syntactic features associated with the verb (de Aguiar et al . ). However, unlike other sentence level treatments (e.g., Thompson et al .…”
Section: Discussionmentioning
confidence: 97%
“…In comparison, de Aguiar et al (2016) is distinctive. It applied a robust technique (random forest) that is novel for the field, and included clinically-relevant variables for simultaneous evaluation.…”
Section: Random Forest Naming Therapy Componentsmentioning
confidence: 84%
“…It is these ingredients that speech and language therapists are most interested in, when designing a therapy to treat a client. With the exception of de Aguiar et al (2016), most reviews tended to either frame their discussions of therapies using broad terminologies like phonological or semantic approaches without examining the specific components; or they may simply narrow their focus and manipulate just one component (e.g., number of treatment items by , but in doing so, forced to commit the non-realistic assumption of ceteris paribus. Consequently, outstanding issues remain unanswered.…”
Section: Reviews and Meta-analysesmentioning
confidence: 99%
See 1 more Smart Citation